Diabetic and Non-Diabetic Gastroparesis: A Retrospective Comparative Outcome Study From the Nationwide Inpatient Sample - Kichloo, Asim (Gastroenterology Res, 2021)
BACKGROUND: Gastroparesis (GP), meaning “gastric palsy”, is a chronic medical condition characterized by delayed or absent gastric emptying in the absence of mechanical obstruction. The primary objective of this study was to determine the patient-specific outcomes and the burden of GP on the US healthcare system. METHODS: This was a population-based, retrospective study designed to analyze data available from the Nationwide Inpatient Sample (NIS) for 2016 and 2017. Using the International Classification of Diseases, Tenth Revision (ICD-10) codes, we identified adult (18 years or older) hospitalizations with a principal diagnosis of GP. The study sample was further classified into two distinct groups based on the presence or absence of GP, namely diabetic GP (DGP) and non-diabetic GP (NDGP). The primary outcome of our study was inpatient mortality secondary to GP while the secondary outcomes included the odds of system-based complications and the burden of the disease on the United States healthcare system. RESULTS: We identified 99,695 adult (≥ 18 years) hospitalizations with a principal discharge diagnosis of GP in 2016 and 2017. Of these patients, 78.1% (77,885) had DGP and 21.9% (21,810) were classified in the NDGP group. We noted a higher proportion of women (79.3% vs. 63.4%, P < 0.001), patients with a history of smoking (35.8% vs. 31.7%, P < 0.001) and chronic obstructive pulmonary disease (10.7% vs. 7.6%, P < 0.001) in the NDGP group. After adjusting for common confounders excluding age, the inpatient mortality for GP was found to be 0.25%. Furthermore, after adjustments were made for the Charlson comorbidity index (CCI), we noted higher odds of mortality in the NDGP group (0.30% vs. 0.23%, adjusted odds ratio (aOR): 3.18, 95% confidence interval (CI): 1.75 - 5.79, P < 0.001) compared to the DGP group. Additionally, patients with NDGP had a higher mean length of stay (5 vs. 4.1 days, P < 0.001) and higher mean total hospital charge ($44,100 vs. $35,500, P < 0.001) compared to those with DGP. The NDGP group also had higher odds of sepsis, deep vein thrombosis (DVT) and pulmonary embolism (PE); however, the odds of developing acute kidney injury (AKI) were lower than that of the DGP group. CONCLUSIONS: The inpatient mortality for GP was found to be 0.25%. After adjusting for CCI, patients with NDGP had higher odds of inpatient mortality compared to the DGP group. Additionally, patients with NDGP were associated with a longer length of hospital stay, mean total healthcare cost and higher odds of complications such as sepsis, DVT and PE during the hospitalization.